CNV analysis in Tourette syndrome implicates large genomic rearrangements in COL8A1 and NRXN1. - Abhishek Nag (Public Library of Science (PLoS), 2013)
Tourette syndrome (TS) is a neuropsychiatric disorder with a strong genetic component. However, the genetic architecture of TS remains uncertain. Copy number variation (CNV) has been shown to contribute to the genetic make-up of several neurodevelopmental conditions, including schizophrenia and autism. Here we describe CNV calls using SNP chip genotype data from an initial sample of 210 TS cases and 285 controls ascertained in two Latin American populations. After extensive quality control, we found that cases (N = 179) have a significant excess (P = 0.006) of large CNV (>500 kb) calls compared to controls (N = 234). Amongst 24 large CNVs seen only in the cases, we observed four duplications of the COL8A1 gene region. We also found two cases with ∼400 kb deletions involving NRXN1, a gene previously implicated in neurodevelopmental disorders, including TS. Follow-up using multiplex ligation-dependent probe amplification (and including 53 more TS cases) validated the CNV calls and identified additional patients with rearrangements in COL8A1 and NRXN1, but none in controls. Examination of available parents indicates that two out of three NRXN1 deletions detected in the TS cases are de-novo mutations. Our results are consistent with the proposal that rare CNVs play a role in TS aetiology and suggest a possible role for rearrangements in the COL8A1 and NRXN1 gene regions.